Virological findings in a case of travel-associated Oropouche virus (OROV) infection imported to Italy, June 2024 - Giada Rossini; Beatrice Mola; Alessandra Rampini; Margherita Ortalli; Giovanna Mattei; Tiziana Lazzarotto (Travel Medicine and Infectious Disease)
Here we report the acute and post-acute virological findings in a OROV infected traveller returning to Italy from Cuba. Testing multiple specimen types and the prolonged detection of OROV RNA in whole blood and urine samples extend the possibility of cases confirmation through direct diagnosis even in convalescence-phase of infection.